PENINGKATAN EFISIENSI PRODUKTIVITAS UMKM KERIPIK TEMPE SAGU “BULANKOE” CILEUNGSI KABUPATEN BOGOR - Perak Samosir (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
The impact of the COVID-19 pandemic in 2020 will be increasingly felt by small industrial business actors in 2021. One of them is the Center for Research and Community Service of the Indonesian Institute of Technology (PRPM ITI), namely the UMKM Tempe Sago Chips "Bulankoe" in Cileungsi. In addition to competition from similar businesses resulting in a decrease in consumer buyers, the main problem is the production process of tempeh chips which still use ordinary knives so that it takes a long time to slice the tempeh. Another problem is the results of the tempeh slices are not evenly thick and thin. If it is too thin, the tempeh slices will crumble when fried and if it is too thick, the tempeh slices are less dry when fried, thereby reducing the amount of production. In order to overcome these problems, the ITI Mechanical Engineering Study Program (PS MS ITI) made a tempeh slicing machine to be donated to UMKM Sago Tempe Chips "Bulankoe" and then provided training on the use of the machine. Through this training activity, UMKM actors are able to operate a tempeh slicing machine, the slicing time is getting faster with the desired thickness.